Surface characteristics of plasma electrolytic oxidation coatings on Cp-Ti and hot-dip aluminised Cp-Ti. (4th May 2022) - Celtik, Cansu; Yurekturk, Yakup; Gecu, Ridvan; Kaboglu, Cihan; Muhaffel, Faiz
ABSTRACT: Plasma electrolytic oxidation (PEO) coatings on commercial pure titanium (Cp-Ti) and hot-dip aluminised Cp-Ti surfaces were prepared in an alkaline electrolyte. The morphological, structural, wear, and corrosion characteristics of the coatings were studied by using SEM, EDS, XRD, electrochemical polarisation, and dry sliding wear tests. The experimental results showed that the main compositions of the PEO coating on Cp-Ti are TiO2 and Al2 TiO5 phases, while the PEO coating on hot-dip aluminised (HDA'ed) Cp-Ti mainly consists of the Al2 O3 phase. The single PEO coating exhibited more porosity with small diameter micro-pores compared to the PEO coating on the HDA'ed sample. Electrochemical polarisation tests revealed that the PEO coating on the HDA'ed sample exhibited approximately 4.6 times more polarisation resistance than the single PEO coating and 10 times that of the bare Cp-Ti sample. According to the wear test results, the wear resistance of the bare Cp-Ti was doubled by hot-dip aluminising (HDA) and PEO treatments, while the single PEO treatment resulted in better resistance against dry sliding wear.